1997
DOI: 10.1017/s0954394500001940
|View full text |Cite
|
Sign up to set email alerts
|

A rural/metropolitan split in the speech of Texas Anglos

Abstract: The migration of people to the Sunbelt in the United States constitutes a major demographic shift, but has received little attention from language variationists. In Texas, this migration has led to a split of the Anglo population of the state into two dialects, a rural dialect and a metropolitan dialect. Evidence from a random-sample survey of Texas and from a systematic set of surveys of high schools in the state shows that young rural Anglos preserve two stereotypical features of the Texas accent, monophthon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
34
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(35 citation statements)
references
References 38 publications
0
34
0
Order By: Relevance
“…In his investigation into the distribution of monophthongal /ay/ and lowered /ey/ (part of the /ey/~/E/ reversal in the Southern Shift) in the speech of Anglos in Texas, Thomas (1997) found a rural/urban split in the use of these two features such that rural Texans were the predominant users of these features while urban Texans tended to exhibit these features least. He associated the non-use of urban Texans with the in-migration of (non-local) Northerners.…”
Section: The Front Vowelsmentioning
confidence: 99%
“…In his investigation into the distribution of monophthongal /ay/ and lowered /ey/ (part of the /ey/~/E/ reversal in the Southern Shift) in the speech of Anglos in Texas, Thomas (1997) found a rural/urban split in the use of these two features such that rural Texans were the predominant users of these features while urban Texans tended to exhibit these features least. He associated the non-use of urban Texans with the in-migration of (non-local) Northerners.…”
Section: The Front Vowelsmentioning
confidence: 99%
“…It is found throughout the South (Brown 1991;Montgomery & Elbe 2004;Tillery & Bailey 2004), though it is also present at scattered points across the US (Metcalf 1972;Bigham 2005;ANAE). In the South, it has been found to be receding recently in large urban centres such as Houston (Koops et al 2008), Dallas and Atlanta (Tillery & Bailey 2004), likely due to a large influx of non-Southerners in the last few decades (Thomas 1997(Thomas , 2004. 4…”
Section: Introductionmentioning
confidence: 99%
“…(Bailey, & Bernstein, 1989;Thomas, 1997). In particular, an acoustic study of Texas Anglo high school students showed lower F2 offset values of /aı/ for rural speakers than metropolitan speakers, suggesting monophthongization in the former group but not in the latter (Thomas, 1997).…”
mentioning
confidence: 98%
“…The phonological characteristics of Southern American English (SAE) as spoken by Texans have been studied in some depth (see Bailey, & Bernstein, 1989;Bailey, & Tillery, 1996;Thomas, 1997). (Bailey, & Bernstein, 1989;Thomas, 1997).…”
mentioning
confidence: 99%